Awareness, knowledge and behavior of medical personnel regarding skin cancer, sun-related hazards and sunscreen utilization at King Abdulaziz University Hospital, Jeddah - Alzahrani, Nujood A.; Fathi, Traji T.; Mortada, Hatan H.; Bukhari, Dania A.; Ashor, Nshwa M.; Mleeh, Nouf T.; Abduljabbar, Mohammed H.; Hariri, Jehad O. (International Journal of Research in Dermatology, 2018)
Background: Worldwide, skin cancer is a major public health concern. It is a common malignancy in Saudi Arabia. The three most prevalent types of skin cancer are basal cell carcinoma, squamous cell carcinoma and melanoma. Exposure to ultraviolet (UV) radiation is the most common modifiable risk factor to lower the risk of the leading types of skin cancer. Practicing protective measures can aid in decreasing the risk of developing skin malignancies. Methods: Data collection took place at King Abdul-Aziz University Hospital, Jeddah, Saudi Arabia. This cross-sectional study was conducted via a structured self-administered questionnaire among medical personnel. Results: The majority (81.9%) of the sample participants were Saudi citizens. Moreover, medical students of 4th year, 5th year and 6th year represented half of the sample. Mean±SD values for the knowledge, behavior, and awareness scores were 6.85±3.31, 8.57±5.00, and 17.75±7.05 respectively. There was no statistically significant difference in mean awareness score for the various categories of demographic variables. One-way-ANOVA revealed statistically significant difference among the different job titles in terms of awareness score with a p value <0.001. Conclusions: The results of this study have shown that the knowledge regarding skin cancer and behavior towards sun exposure is inadequate. Therefore, increasing the knowledge in the form of awareness campaigns is highly recommended.